Effects of pressure on the root systems of Norway spruce plants (Picea abies[L.] Karst.) - R. Gebauer; M. Martinková (Journal of Forest Science, 2005)
Roots are stressed quire often under natural conditions, e.g. when considering sloping terrain, layers of fluvial deposits, huge layers of melting snow, load of heavy forest machinery during logging and hauling operations, recreational activities of people, high density of deer or cattle, etc. We focused our experiments on Norway spruce (Picea abies[L.] Karst.) seedlings grown in containers with glass walls under the permanent load of 5.1 kPa during the whole growing season. The applied pressure affected roots both directly and indirectly due to the occurrence of hypoxia. Root growth ceased under such conditions. Growth dynamics and capability to occupy available soil also changed. For example, the total root area of experimental plants decreased to 52% but the root area index (RAI) was higher by 33% when compared to the control. It indicates that the pressure applied to the soil surface caused the development of only smaller root systems but more compacted into smaller volumes of soil. Mean longitudinal growth of stressed roots decreased by about 50% when compared to the control. Growth of experimental roots was also delayed, which is a typical general response to stress. However, a tendency to create dense and small root systems is in contradiction with the typical strategy of tree root systems.